The influence of subdivision design and conservation of open space on carbon storage and sequestration (2014)
Cities are increasingly trying to offset carbon dioxide emissions and existing and new residential developments, or urban subdivisions, are a major source of such emissions. Compact or clustered subdivision designs have the potential to improve carbon storage and sequestration through the conservation of open space and the preservation of existing trees found on built lots. However, very few empirical studies assess how different subdivision designs and tree preservation strategies affect the carbon footprint of proposed residential developments. Using a 705 ha pine plantation that has been approved for the development of 1835 residential units near Gainesville, Florida, our objectives were to determine which site designs and tree preservation strategies could maximize carbon sequestration and storage. From 80 stratified random plots, we measured and analyzed tree and plot characteristics according to forest type and tree stand age categories. Tree data collected from these plots were analyzed with the i-Tree ECO model to estimate baseline predevelopment carbon stores and sequestration rates. Using ArcMap, we then assessed the impact, on baseline carbon sequestration and storage capacity, of several different site designs and tree conservation scenarios for the proposed development. Up to 91% of carbon storage and up to 82% of carbon sequestration could be maintained through a cluster urban development design and by preserving older tree stands. Results indicate that a subdivision's carbon footprint can significantly improve when forest types and tree preservation are incorporated into the design of a development.